2019
DOI: 10.3390/jcm8071038
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Lung Cancer Therapeutic Responses Through Fractal Measurements: From Radiology to Mitochondrial Biology

Abstract: Small cell lung cancer (SCLC) is an aggressive neuroendocrine disease with an overall 5 year survival rate of ~7%. Although patients tend to respond initially to therapy, therapy-resistant disease inevitably emerges. Unfortunately, there are no validated biomarkers for early-stage SCLC to aid in early detection. Here, we used readouts of lesion image characteristics and cancer morphology that were based on fractal geometry, namely fractal dimension (FD) and lacunarity (LC), as novel biomarkers for SCLC. Scanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
(103 reference statements)
0
8
1
Order By: Relevance
“…In this study, the quantification of the differences between the studied samples was verified for the first time using the FD, lacunarity, and several GLCM textural parameters of the follicular cell nuclei. In contrast with many earlier findings, which have demonstrated a higher chromatin FD in various tumor tissues (Sedivy et al, 1999;Dey & Mohanty, 2003;Mashiah et al, 2008;Bedin et al, 2010;Ferro et al, 2011;Huang et al, 2012;Jabalee et al, 2018;Mambetsariev et al, 2019;Metze et al, 2019), the results of our current study showed a lower chromatin FD in tumor tissues than in the corresponding benign tissues. Chromatin is divided into two distinct regions based on the gene density: (i) euchromatin (uncondensed and gene-rich conformation) and (ii) heterochromatin (condensed and gene-poor conformation).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, the quantification of the differences between the studied samples was verified for the first time using the FD, lacunarity, and several GLCM textural parameters of the follicular cell nuclei. In contrast with many earlier findings, which have demonstrated a higher chromatin FD in various tumor tissues (Sedivy et al, 1999;Dey & Mohanty, 2003;Mashiah et al, 2008;Bedin et al, 2010;Ferro et al, 2011;Huang et al, 2012;Jabalee et al, 2018;Mambetsariev et al, 2019;Metze et al, 2019), the results of our current study showed a lower chromatin FD in tumor tissues than in the corresponding benign tissues. Chromatin is divided into two distinct regions based on the gene density: (i) euchromatin (uncondensed and gene-rich conformation) and (ii) heterochromatin (condensed and gene-poor conformation).…”
Section: Discussioncontrasting
confidence: 99%
“…Quantitative morphologic interpretation of the stained histologic sections or cytologic preparations may be done by basic morphometry and sophisticated texture analysis based on digitalized images (Ferreira et al, 2006; Metze et al, 2009, 2019; Metze, 2013). Among these medical image analyses, the fractal and GLCM textural analyses have shown to be of increasing importance particularly for the investigation of various tumor types (Sedivy et al, 1999; Dey & Mohanty, 2003; Mashiah et al, 2008; Bedin et al, 2010; Ferro et al, 2011; Huang et al, 2012; Jabalee et al, 2018; Mambetsariev et al, 2019). It is well known that HT and PTC specimens sporadically share the same morphological features, immunohistochemical staining, and molecular profiles (Arif et al, 2002; Weetman, 2004; Rhoden et al, 2006; Ohmori et al, 2007; Anand et al, 2014); therefore, the differential diagnosis between the HT-alone and the HT-associated PTC specimens is not always easy, even for a trained observer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] reviewed the role fractal dimension and found that FD increases in carcinogenesis. In addition, FD has been used for the classification of breast tumors,[ 19 ] in therapeutic response of small cell lung cancer[ 20 ] and to differentiate benign and malignant thyroid nodule. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients is extremely poor and the mortality rate is very high. About two-thirds of SCLC patients are diagnosed at the extensive stage (ES) [3], and the median survival time of ES-SCLC patients is about 9.4-12.8 months, and the survival rate is between 5.2%-19.5% [4,5]. However, almost all patients will suffer recurrence and metastasis within 1-2 years after standard first-line treatment.…”
Section: Introductionmentioning
confidence: 99%